A bifunctional catalyst based on a carbon quantum dots/mesoporous SrTiO3 heterostructure for cascade photoelectrochemical nitrogen reduction. Issue 23 (1st June 2022) - Hu, Yongming; Zhao, Zhi Liang; Ahmad, Rafia; Harb, Moussab; Cavallo, Luigi; Azofra, Luis Miguel; Jiang, San Ping; Zhang, Xinyi
Abstract : An ultrathin carbon quantum dots modified hydrogenated mesoporous SrTiO3 heterostructure (CQDs/STO) has been developed as a bifunctional catalyst for enhanced photoelectrochemical nitrogen reduction, resulting in a ∼50% increase in the ammonia yield. Abstract : Despite considerable progress in the field of sustainable ammonia technology, the low efficiency and yield have remained the main bottleneck in artificial nitrogen fixation under ambient conditions. In this work, an ultrathin carbon quantum dot modified hydrogenated mesoporous SrTiO3 heterostructure (CQDs/STO) has been developed as a bifunctional catalyst for enhanced nitrogen reduction. CQDs/STO exhibits a high photocatalytic activity and an ammonia yield of 143 μmol g −1 h −1 has been achieved without any sacrificial reagent, which is about 7 times that of STO nanoparticles. Furthermore, we demonstrate that CQDs/STO can be utilized as a bifunctional catalyst for cascade photoelectrochemical nitrogen reduction, resulting in a ∼50% increase in the ammonia yield. DFT calculations reveal that the synergy between SrTiO3 and CQDs has the capability for photocatalytic reduction of N2 with the O-vacancies in SrTiO3 playing a key role also as electrocatalytic centers. We believe that such a cascade catalytic system provides a new insight into designing photoelectrochemical devices for solar-driven nitrogen fixation.